EQUATIONS OF PLANETARY SYSTEMS MOTION - Minglibayev, M. Zh.; Kosherbayeva, A.B. (Academic Scientific Journal of Computer Science, 2020)
The study of the dynamically evolution of planetary systems is very actually in relation with findings of exoplanet systems. N free spherical bodies problem is considered in this paper, mutually gravitating according to Newton’s law, with isotropically variable masses as a celestial-mechanical model of non-stationary exoplanetary systems. The dynamic evolution of planetary systems is learned, when evolution’s leading factor is the masses’ variability of gravitating bodies themselves. The laws of the bodies’ masses varying are assumed to be known arbitrary functions of time. When doing so the rate of varying of bodies’ masses is different. The planets’ location is such that the orbits of planets don’t intersect. Let us treat this position of planets is preserve in the evolution course. The motions are researched in the relative coordinates system with beginning in the center of the parent star, axes that are parallel to corresponding axes of the absolute coordinates system. The canonical perturbation theory is used on the base aperiodic motion over the quasi-canonical cross-section. The bodies evolution is studied in the osculating analogues of the second system of canonical Poincare elements. The canonical equations of perturbed motion in analogues of the second system of canonical Poincare elements are convenient for describing the planetary systems dynamic evolution, when analogues of eccentricities and analogues of inclinations of orbital plane are sufficiently small. It is noted that to obtain an analytical expression of the perturbing function main part through canonical osculating Poincare elements using computer algebra is preferably. If in expansions of the main part of perturbing function is constrained with precision to second orders including relatively small quantities, then the equations of secular perturbations will obtained as linear non-autonomous system. This circumstance meaningful makes much easier to study the non-autonomous canonical system of differential equations of secular perturbations of considering problem.